The problems of mental causation and pluralist alternatives - Hoffmann, Stephanie Lee, author; MacKenzie, Matthew, advisor; Kasser, Jeffrey, committee member; Richards, Tracy, committee member (Colorado State University. Libraries, 2015)
The mental causation literature tends towards certain presuppositions, including the tacit endorsement of physicalism, causal closure, and reductionism. Insofar as justification for these philosophical positions is offered at all, it is typically claimed that they are grounded in actual scientific practice. However, there are good reasons to believe that actual science does not support these philosophical positions. In this work, I consider some reasons to deny physicalism and causal closure, and critically present and evaluate pluralistic alternatives to reductionism. In light of this discussion, the problem of mental causation takes on an interesting and promising new form.
Keywords: physicalism; mental causation; pluralism